Kie Dan Pengobatan Berbagai Penyakit Kulit Di Wilayah Kerja Puskesmas Pauh Padang - Satya Wydya Yenny (Jurnal Pengabdian Warta Andalas, 2016)
Infectious skin disease consists of a skin disease caused by bacterial, fungal, viral, and parasitic infestations. Consultation Educational and Information of Various Skin Disease in Pauh Public Health, Padang aimed to increase the knowledge and public awareness on infectious disease, especially fungal infections